2012
DOI: 10.1017/s1368980012004314
|View full text |Cite
|
Sign up to set email alerts
|

Use of food supplements and determinants of usage in a sample Italian adult population

Abstract: Objective: The aims were to collect data on consumption of different food supplements in a sample of the adult Italian population and to characterize users by demographic, physical and health-related characteristics, lifestyle and behaviour. Design: Cross-sectional survey. Setting: The study was conducted in 2008 in ten towns of Italy (two towns from each of the five macro-areas: Northwest, Northeast, Centre, South and Islands). Subjects: Adults (n 10 000) aged $18 years were randomly selected and asked to fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 31 publications
7
47
2
1
Order By: Relevance
“…A study in the USA found that older people had been associated with greater likelihood of consuming multivitamin-multimineral supplements (Rock, 2007). However, a study conducted in Italy found negative association between age and consumption of food supplements (Giammarioli et al, 2013). One might hypothesize that the existence of chronic diseases or health condition would make older people to be more motivated to use dietary supplement as a complement to disease treatments (Denison et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A study in the USA found that older people had been associated with greater likelihood of consuming multivitamin-multimineral supplements (Rock, 2007). However, a study conducted in Italy found negative association between age and consumption of food supplements (Giammarioli et al, 2013). One might hypothesize that the existence of chronic diseases or health condition would make older people to be more motivated to use dietary supplement as a complement to disease treatments (Denison et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the relationship between health status and supplement use, contradictory results have been reported (13,14,38,39) . These discrepancies may be due to differences in the study populations, the definitions of supplements and the assessment methods.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to previous surveys, in which elderly women were more likely to use multiple supplements [28]- [31]. One reason for this discrepancy could be the inclusion of drugs containing calcium and vitamin D, which are more often consumed by women due to osteoporosis prophylaxis, in former studies [2] [8] [29]. Overall, multiple use played a minor role when considering the totality of subjects.…”
Section: Discussionmentioning
confidence: 76%